PENINGKATAN AKTIVITAS BELAJAR MAHASISWA PADA MATA KULIAH EVALUASI HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK - Imelda Imelda (Universitas Islam Sumatera Utara, 2017)
This research is a classroom action research. The objectives of this research are: (1) to describe student's learning activity in project-based learning; (2) to describe the improvement of student learning activity of mathematics education program of St. Thomas University through the application of project-based learning model; (3) to analyze student project tasks in project-based learning. The results of this study indicate that student learning activity in cycle 1 is 41.66% active students in visual activities, 25% active students in oral activities, 47.22% active students in writing activities, 13.89% active students in mental activities. Students activity in cycle 2 is 75% active students in visual activities, 63.89% active students in oral activities, 75% active students in writing activities, 52.78% active students in mental activities. The test validity test consisted of 18 tests tested in 18 schools with a total of 90 questions in which each test consisted of 4 questions, 5 questions and 6 questions. Validity results obtained 69 problems (76.67%) valid and as many as 21 problems (23.33%) is invalid. The results of the test reliability obtained 12 reliable tests with high reliability category as many as 5 tests (27.78%) and medium relative category as many as 7 tests (38.89%) and there are 6 tests (33.33%) that are not reliable. The result of analysis of different test variables obtained 39 problem (43,33%) with bad category, 29 problem (32,22%) enough category, and 16 problem (17,78%) good category. The results of the analysis of the difficulty level of the test obtained that from 90 tested questions there are 42 easy questions, 45 problems medium and 3 difficult questions.